Sejarah Perkembangan Ilmu di Barat dan Islam dengan Penalaran Bayani Irfani dan Burhani Bagi Pengembangan Ilmu Pendidikan Agama Islam - Hanasto, Hanasto; Usman, Usman; Sibawaihi, Sibawaihi (LPPM Institut Pendidikan Nusantara Global, 2025)
This study explores the historical and philosophical development of scientific knowledge in both Western and Islamic civilizations. The trajectory of science in the West reveals a complex evolution, beginning with Ancient Greek civilization, continuing through the Medieval period, the Renaissance, the Modern era, and into the Contemporary age marked by Nietzsche's philosophy and rapid technological advancement. Each historical phase reflects shifting paradigms influenced by philosophical, social, and political contexts. In contrast, the Islamic civilization reached its intellectual zenith during the Umayyad and Abbasid dynasties. This period was characterized by territorial expansion, a vigorous translation movement, and significant advancements in various scientific fields. Muslim philosophers promoted an integrative approach to knowledge, emphasizing proper methodologies for acquiring truth and applying it to practical life. Their openness to knowledge, regardless of its originas expressed by al-Kindi’s assertion that truth should be accepted even from distant nations illustrates the inclusive spirit of Islamic scientific thought. Overall, the study underscores that the progress of science is a product of dynamic cross-civilizational interaction, driven by a universal pursuit of truth.